MODEL PEMBELAJARAN TWO STAY TWO STRAY PADA MATA PELAJARAN QUR’AN HADIS DI MADRASAH IBTIDAIYAH - Nasution, Zulkipli (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2021)
The Two Stay Two Stray learning model is one of the cooperative learning models. This model can be used during the covid-19 pandemic in the form of group collaboration. This article aims to describe how the Two Stay Two Stray learning model is in the Qur'an Hadith subjects, how the steps of the Two Stay Two Stray learning model at Madrasah Ibtidaiyah along with its advantages and disadvantages. The two stay two stray (TSTS) learning model requires students to be more active and students are led to work together in solving problems. When using this strategy, educators can also add additional methods as support to make it more varied.